Preparation of hyperbranched polymers by controlled/living polymerisations - Zheng, Yu (2010)
This thesis describes the development of a novel route for preparation of hyperbranched polymers. The aim is to produce hyperbranched polymers via enhanced deactivation ATRP without crosslinking even at high conversion. Our strategy will be to use excess Cu(I1) to control gelation, so called enhanced deactivation ATRP. Chapter I provides a general introduction to the basic concepts of living polymerisation and dendritic polymers. Chapter 2 covers the hyperbranched homopolymer prepared by enhanced deactivation ATRP. The hyperbranched poly(divinylbenzene) and poly(ethylene glycol dimethacrylate) are synthesised by enhanced deactivation ATRP in a concentrated system. Chapter 3 focuses on the synthesis of hyperbranched copolymer via the enhanced deactivation ATRP. Also. the interesting potential applications, for example dye encapsulation and viscosity control are explored in this chapter. Chapter 4 demonstrates two routes to prepare novel core-shell polymers. First, the hyperbranched polyDYB was used as a core to produce hyperbranched core-shell polymers. Second, a novel hyperbranched polymer which combines ring open polymerisation and RAFT technique was developed. Chapter 5 summarises all the research presented in this thesis. Moreover, some possible research routes for the investigation in the future are listed in this part.